2023
DOI: 10.1186/s12903-023-02840-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oral health literacy on dental anxiety and utilization of oral health services among dental patients: a cross sectional study

Abstract: Background Low oral health literacy levels and deficient oral health knowledge jeopardize the communication between dentists and patients in different communities. This study aimed to examine the impact and association of oral health literacy with patients’ levels of dental anxiety and their utilization of dental health services. Methods This cross-sectional study was conducted at the Misr International University (MIU) dental clinics. The study ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
2
8
1
Order By: Relevance
“…6 In the present study, there were more female 125 [6][7][8][9] Since many private schools prefer female teachers there is a difference in the distribution of male and female teachers. The oral health status and treatment needs of a sample of school teachers of the Kathmandu district were assessed and it was found that the prevalence of dental caries was 98 (59.4%) which is in accordance with the findings of Mary et al 6 but in contrast to the study done by Sunitha et al 10 Although studies 11,12 have shown that teachers have good knowledge about aetiology of dental caries, the prevalence is still high. This may be because they are not motivated enough to follow better oral hygiene practices.…”
Section: Discussionsupporting
confidence: 80%
“…6 In the present study, there were more female 125 [6][7][8][9] Since many private schools prefer female teachers there is a difference in the distribution of male and female teachers. The oral health status and treatment needs of a sample of school teachers of the Kathmandu district were assessed and it was found that the prevalence of dental caries was 98 (59.4%) which is in accordance with the findings of Mary et al 6 but in contrast to the study done by Sunitha et al 10 Although studies 11,12 have shown that teachers have good knowledge about aetiology of dental caries, the prevalence is still high. This may be because they are not motivated enough to follow better oral hygiene practices.…”
Section: Discussionsupporting
confidence: 80%
“…The internal consistency measured through Cronbach's alpha is high and quite similar to the value found in the original validation study for the HeLD-14 [14] and in studies assessing the validity and reliability of the Brazilian and Chinese versions of the HeLD-14 [16,17]. Moreover, the value is higher than the one found in the other study using an Arabic version of HeLD-14, which obtained a Cronbach's alpha of 0.76 [20].…”
Section: Correlation Matrixsupporting
confidence: 79%
“…The investigators aimed to assess the OHL among schoolteachers. However, the study did not present much information on the validity and reliability of the instrument [20]. A valid and reliable version of an Arabic version of the HeLD-14 is thus needed and relevant to introduce.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…11,12 There is significantly high burden of oral diseases that are preventable and OHL has been associated with reduced incidence of oral diseases. 13,14 Moreover, primary, secondary, and tertiary prevention strategy implementation to population may not help to improve oral health until and unless people get individual attention toward improvement. 15,16 Hence, OHL is a crucial factor in promoting and maintaining good oral health.…”
Section: Introductionmentioning
confidence: 99%